Academisation or Vocational drift? : International developments in the tertiary sector of education - Hippach-Schneider, Ute [Verfasser] (My University, 2014)
"OECD data for the period from 1995 to 2010 point to an enormous upturn in participants in academic courses. At the same time, vocational and practice-related training courses in the tertiary sector of education are stagnating. The question addressed in the article is how far it is justified, against this backdrop, to speak about academicisation, or whether it is not rather the case that the detailed content of tertiary education programmes is drifting in a 'vocationally oriented' direction." (Authors' abstract, BIBB-Doku)
Keywords: S 1.4 Hochschulbildung; 370; Akademisierung; Bildungsangebot; Hochschule; Berufsbezug